Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Pembelian Ulang Pada Kopi Kenangan Singaraja - Sukmawati, Sukmawati; Yulianthin, Yulianthin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the influence of (1) product quality on repeat purchases, (2) service quality on repeat purchases, and (3) product quality and service quality on repeat purchases at Kopi Kenangan Singaraja. The sample in this study consisted of 140 respondents. The research method used was quantitative causal with multiple linear regression analysis. The results of this study indicate that: (1) product quality has a positive and significant effect on repeat purchases at Kopi Kenangan Singaraja, (2) service quality has a positive effect on repeat purchases at Kopi Kenangan Singaraja, and (3) product quality and service quality have a positive and significant effect on repeat purchases at Kopi Kenangan Singaraja.